Digital Literacy and Academic Literacy for a University in Transformation - Bruno, Amada (2019)
University students are immersed in a world of technologies and social networks that modify their daily and academic practices. Therefore, the concept of literacy must be redefined according to the basic competences and skills that are necessary in this digital culture. At the same time, in the context of university education in Latin America, data registered by the World Bank indicate that in the last years the number of students enrolled at university doubled, while the rate of graduated students dropped sharply. This may evidence the incapacity of university institutions to retain students, among other things. Argentina is not divorced from this reality as it shows high enrollment rates, together with low graduation rates. The purpose of this article is to analyze only two aspects of this issue which, in turn, may contribute to explain this context. On the one hand, we try to explain digital literacy, which implies using information and communication technologies to interpret and critically select the endless amount of information that is in the net; and on the other hand we try to explain academic literacy, which helps students to be part of the university culture.